Pan africanism and its ambivalences in the african methodist episcopal church in South africa 1896- 1920s - Mashingaidze, Terence M. (Midlands State University, 2015)
Some scholars of Christianity in Africa have viewed the African Methodist Episcopal Church‘s (AMEC) incorporation of Reverend Mangena Mokena’s Ethiopian Church as its South African branch in 1896 through the Afrocentric lens, perceiving it as an early manifestation of people of African descent’s sense of common identity and shared destiny. The consciousness of race uplift and solidarity that pervaded this trans-Atlantic union fits the standard morphology of Pan-Africanist synergies. Significantly, African American missionaries often stated that they sympathised with African church secessionists largely because they found much in South African Christianity that resembled the factors and practices that impelled the birth of AMEC. While the African Americans articulated Pan-African ideals and expressed a desire to identify with Africans, I argue, their conduct and language occasionally alienated them from Africans‘ experiences and concerns. When they encountered Africans in South Africa they did not fully appreciate local political aspirations and economic demands. They marginalised their fellow African communicants. Some even looked down upon Africans and frustrated local struggles against white exploitation. Other AMEC resident bishops threatened to expel African church leaders and laity that dabbled in politics. This was quite blasé, I conclude, considering that some of these indigenous churchmen constituted the educated elite who felt morally compelled to speak for and organise their people against unjust and racist policies of the white South African government.